USAID & CCAFS webinar: Can we reduce GHG emissions from livestock? A feasibility and investment study from East Africa - Gurwick, Noel; Wollenberg, Eva Karoline; Ericksen, Polly J.; Crane, Todd A.; Kihoro, Esther; Vernooij, Vera; Onyango, Joel; Tavenner, Katie; Schoneveld, George C.; Vellema, Sietze R.; Atella, Joanes (2019)
Agenda: Intriduction of series - Noel Gurwick (USAID) Livestock in East Africa: an overview - Lini Wollenberg (CCAFS, UVM) Low emission investment options for the dairy sector: The case of improved fodder production - Polly Ericksen (ILRI) Understanding pathways toward low emissions livestock: Evidence from Kenya and Tanzania - Todd Crane (ILRI)